RADIATION EXPOSURE IN INTERVENTIONAL CARDIOLOGY: STRATEGIES FOR REDUCTION AND PROTECTION - KAMAL , A; KHAN , MAUR; SADIQ , NS (Biological and Clinical Sciences Research Journal, 2023)
Occupational radiation exposure is a significant concern among healthcare professionals, particularly those in interventional radiology and cardiology procedures. This study aims to comprehensively investigate radiation exposure and its health effects among 200 healthcare professionals, including 100 physicians, 50 nurses, and 50 technicians, across five hospitals. The study employed a controlled, multi-center, observational design, with 100 participants in the experimental group exposed to enhanced radiation protection strategies, while 100 participants in the control group adhered to standard safety protocols. The interventions included additional lead barriers, radiation-absorbent pads, real-time dose monitoring systems, and continuous staff training on radiation safety. Exposure levels were measured using personal dosimeters at regular intervals before and after the interventions. Subgroup analysis was conducted based on professional roles and procedure types, categorized into simple and complex interventions. The results showed a statistically significant reduction in annual radiation exposure in the experimental group compared to the control group, with substantial effect sizes. Subgroup analysis revealed varying degrees of exposure reduction among different professional roles. Notably, complex interventions demonstrated the most substantial reductions in radiation exposure. Furthermore, an analysis of X-ray beam angles indicated a statistically significant increase in exposure at steep angles (≥30°). However, no significant interaction between the control and experimental groups was observed, suggesting that other variables may influence the relationship between steep angles and exposure. The findings of this study emphasize the effectiveness of enhanced protection strategies in reducing occupational radiation exposure among healthcare professionals. The nuanced effects observed across different professional roles and procedure types underscore the importance of tailored safety measures. These results contribute to the ongoing efforts to optimize radiation safety in medical settings and promote the well-being of healthcare professionals. Ethical considerations, adherence to international standards, and the potential implications for policy and guidelines further underscore the significance of this study's findings.